2010
DOI: 10.1099/vir.0.024984-0
|View full text |Cite
|
Sign up to set email alerts
|

Covalent modification by SUMO is required for efficient disruption of PML oncogenic domains by Kaposi's sarcoma-associated herpesvirus latent protein LANA2

Abstract: The multifunctional Kaposi's sarcoma-associated herpesvirus (KSHV) latent protein latencyassociated nuclear antigen 2 (LANA2) has a critical role in KSHV-induced B-cell malignancies. LANA2 increases the level of small ubiquitin-like modifier (SUMO)2-ubiquitin-modified PML and induces the disruption of PML oncogenic domains (PODs) by a process that requires a noncovalent SUMO interaction domain (SIM) in LANA2. We now demonstrate that LANA2 is covalently conjugated to SUMO1 and SUMO2 both in vitro and in latentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 38 publications
4
26
0
Order By: Relevance
“…Specifically, expression of vIRF3 increases the levels of SUMO2 ubiquitination-modified promyelocytic leukemia (PML) gene product oncogenic domains (PODs) (31). Furthermore, vIRF3 is covalently conjugated to SUMO1 and SUMO2 in vitro and in KSHV latently infected B cells (32). vIRF3 is also capable of inhibiting SUMOylation of the pRb proteins pRb, p107, and p130 (33).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, expression of vIRF3 increases the levels of SUMO2 ubiquitination-modified promyelocytic leukemia (PML) gene product oncogenic domains (PODs) (31). Furthermore, vIRF3 is covalently conjugated to SUMO1 and SUMO2 in vitro and in KSHV latently infected B cells (32). vIRF3 is also capable of inhibiting SUMOylation of the pRb proteins pRb, p107, and p130 (33).…”
Section: Discussionmentioning
confidence: 99%
“…11 Therefore, we evaluated the conjugation of p53 to SUMO2 in HEK-293 cells co-transfected with pcDNA, LANA2-WT, a LANA2 mutant in the SIM domain (LANA2DSIM), a SUMOylation mutant (LANA2DSUMO), or the double SIM and SUMOylation mutant of LANA2 (LANA2TOTAL), together with an empty vector or Ubc9 and His6-SUMO2. Expression of LANA2-WT induced a reduction in the levels of p53-SUMO2 that was less evident after expression of LANA2DSIM or LANA2DSUMO, and almost undetectable after expression of LANA2TOTAL ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Viruses can counteract or enhance the host's sumoylation to evade the immune response and antagonize apoptosis, while some viruses exploit the host's sumoylation machinery to sumoylate the viral components which are necessary to perform viral functions (48). It has been reported that KSHV modulates the SUMO pathway through RTA/ORF50, K-bZIP/K8, and vPK/ORF36 during lytic replication as well as LANA/ORF73 and viral IRF3 (IRF3)/K10.5/LANA-2 during latency (27,35,(49)(50)(51)(52)(53)(54)(55)(56). Our results showed that LANA bound directly to the SENP6 promoter and repressed its activity, inhibiting SENP6 expression at both the RNA and protein levels.…”
Section: Discussionmentioning
confidence: 99%